2017
DOI: 10.3892/mco.2017.1261
|View full text |Cite
|
Sign up to set email alerts
|

Modified glasgow prognostic score in patients with small-cell lung cancer

Abstract: Abstract. Systemic inflammatory response, which represents the presence of cachexia, is observed often in patients with lung cancer. To evaluate the prognostic significance of the presence of a systemic inflammatory response in small cell lung cancer (SCLC) patients, a retrospective study using modified Glasgow prognostic Score (mGPS) was performed. This score is composed of serum albumin and C-reactive protein levels. All the patients with SCLC who were diagnosed in Tsukuba

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 16 publications
3
32
0
Order By: Relevance
“…Two studies showed mGPS as an independent prognostic factor for OS in SCLC patients. 6 , 16 Although their patient backgrounds were different from ours, their result was consistent with ours. Compared with our study, including 33% (n=32) of mGPS 2, the proportions of mGPS 2 were much lower in those two previous studies: a Chinese and a Japanese study included only 3.1% (n=11) 6 and 22.9% (n=73), 16 respectively.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Two studies showed mGPS as an independent prognostic factor for OS in SCLC patients. 6 , 16 Although their patient backgrounds were different from ours, their result was consistent with ours. Compared with our study, including 33% (n=32) of mGPS 2, the proportions of mGPS 2 were much lower in those two previous studies: a Chinese and a Japanese study included only 3.1% (n=11) 6 and 22.9% (n=73), 16 respectively.…”
Section: Discussionsupporting
confidence: 88%
“… 6 , 16 Although their patient backgrounds were different from ours, their result was consistent with ours. Compared with our study, including 33% (n=32) of mGPS 2, the proportions of mGPS 2 were much lower in those two previous studies: a Chinese and a Japanese study included only 3.1% (n=11) 6 and 22.9% (n=73), 16 respectively. Unlike our study that enrolled patients treated with chemotherapy alone, the Chinese study included 46.2% of patients treated with thoracic radiotherapy 6 and the Japanese study included 13.5% patients treated with supportive care alone.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study design may have resulted in a loss in the identification of tumour type‐specific compounds, but this huge data‐noise has been able to identify trans‐tumoral differences associated with cancer cachexia. Other studies have shown gender differences in metabolic regulation, treatment‐related mortality, and progression of cachexia, being the female sex a favourable prognostic factor . Our study was not designed to evaluate the effect of gender in the genesis nor the evolution of cancer‐related cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of cachexia is characterized by a negative energy balance in the body resulting from a combination of inadequate energy intake (anorexia), increased energy expenditure, and systemic inflammation, but abnormal metabolism is the major component . All together result in a clinical phenotype characterized by muscle wasting and body weight loss .…”
Section: Introductionmentioning
confidence: 99%